Method for recycling polyester nonwoven fabric into staple fibers
Patent Information
- Application Number
- JP2023560352
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-02
- Filing Date
- 2022-03-31
- Publication Date
- 2025-03-12
AI Technical Summary
Recycling polyester-based nonwoven fabrics containing PET/coPET low-melting fibers results in materials with unpredictable and lower viscosity properties, making them unsuitable for direct reuse in nonwoven manufacturing processes, and existing methods to increase intrinsic viscosity are costly.
A method involving re-pelletizing nonwoven fabrics to produce recycled polyester pellets, blending them with virgin polyester flakes, and extruding the mixture into polyester staple fibers, which maintains or enhances the intrinsic viscosity and melting temperature, allowing for the production of high-quality nonwoven materials.
The method produces polyester staple fibers with enhanced intrinsic viscosity and melting temperature, enabling their use in nonwoven fabrics with properties comparable to virgin fibers, suitable for various applications including sanitary products and automotive components.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for recycling polyester-based nonwoven fabrics containing 5-50% sheath / core or side-by-side or other PET and / or coPET low melting fibers into new fibers. [Background technology]
[0002] Polyethylene terephthalate, commonly abbreviated as PET, is the most common thermoplastic polymer resin of the polyester family, used in combination with glass fibers to make engineering resins, for thermoforming to make fibers or yarns for clothing or nonwovens, containers for liquids and food.
[0003] It is known to recycle PET food containers, mainly bottles, into pellets, flakes or chips to produce fibers for use in nonwoven materials. PET bottles are made of virtually pure PET homopolymer, and the properties of the fibers obtained after recycling are only slightly modified compared to virgin PET fibers, making them easier to use further.
[0004] This is not the case for other PET raw materials. In particular, in the nonwoven industry, PET homopolymers are associated with PET copolymers (coPET) in a core-sheath association, either as a mixture of fibers or even as a mixture within a single fiber. For example, thermally bonded drylaid nonwovens contain 5-60% low melting PET / coPET fibers as a binder. A single product, e.g. hygiene products, further combines several different layers of nonwovens.
[0005] Because the ratio between PET / coPET is variable, the resulting products obtained from recycling nonwoven waste have variable / unpredictable properties, usually having lower viscosity and lower melting temperature than virgin (non-recycled) materials.
[0006] Nevertheless, the applicant wishes to address the issue of recycling nonwoven waste, which can be of two types: post-industrial waste or post-consumer waste. Post-industrial waste mainly comes from the nonwoven manufacturing process or the process of including nonwovens in further articles. Post-consumer waste refers to refined, cleaned or washed waste from the final consumer. In order to maximally reduce the ecological impact of recycling nonwovens, it is desired to reach circularity, i.e. to recycle to new fibers to produce nonwovens, preferably on-site or with limited transportation. Summary of the Invention
[0007] To this end, the present invention relates to a method for recycling polyester-based nonwoven fabrics containing 5-60% PET / coPET low melting point staple fibers, the method comprising: - feeding the polyester nonwoven fabric for recycling to a re-pelletizer to obtain recycled polyester pellets; - mixing the resulting pellets with polyester flakes to obtain a blend containing 15-35% recycled polyester-based pellets and 65-85% polyester flakes; and - extruding the blend into polyester staple fibers (PSF).
[0008] The polyester flake can be "virgin" polyester flake (or chip), but preferably the polyester flake is derived from recycled (post-industrial) PET bottles.
[0009] PET / coPET preferably refers to a mixture of PET and coPET, i.e., a mixture of PET homopolymer and copolymer, as explained above, in a core-sheath association, as a mixture of fibers, or even as a mixture within a single fiber.
[0010] Polyester is intended to refer to any type of polyester and derivatives (PBT, PTT...), i.e. aliphatic homo- or copolyesters, as well as aromatic homo- or copolyesters, or mixtures thereof, whatever the source of the polyester, including recycled polyesters and polyesters derived from said environmentally friendly sources.
[0011] The polyester-based nonwovens that are recycled can take a variety of forms depending on their origin. They can be, for example, press bale shredded nonwoven, over press bale nonwoven trim, non-press trim or off-spec rolls.
[0012] Low melting staple fibers (LMF) refer to fibers that have at least a sheath component that melts at a low temperature (i.e., a melting temperature of about 180°C or less, preferably a melting temperature of about 160°C or less, preferably a melting temperature of about 130°C or less, more preferably a melting temperature of about 110°C or less) and function as a binder for other fibers with higher melting points in the nonwoven fabric manufacturing process. Low melting staple fibers usually have a fineness of 1 dn to 30 dn, but can also have a larger fineness. LMF usually has a core / sheath structure, but this is not required.
[0013] The polyester staple fibers (PSF) obtained by the process of the present invention are standard PSF, with finenesses varying from 0.5 dn to 40 dn, preferably from 1.5 dn to 15 dn. These PSF contain 0.75 to 17.5% PET and / or coPET (derived from recycled nonwovens). Preferably, these PSF fibers have a melting point above 180°C, preferably above 200°C, even more preferably above 240°C, possibly between 245°C and 255°C.
[0014] The polyester staple fibers containing at least 0.75% of PET and / or CoPET obtained by the method of the present invention, i.e. originating from recycled nonwoven fabrics, can be distinguished from normal polyester staple fibers by their low intrinsic viscosity of less than 0.7 dl / g, preferably between 0.6 and 0.7 dl / g, which for white fibers is for example between 0.65 and 0.70 dl / g, whereas for black fibers it can drop to for example about 0.62 dl / g.
[0015] Advantageously, the polyester staple fibers (PSF) obtained by the process of the invention are further used to manufacture a nonwoven fabric, preferably a 100% polyester nonwoven fabric, more preferably a 100% polyester staple fiber nonwoven fabric. Thus, a further step of the process of the invention is - A process in which PSF is incorporated into a web of fibers to produce a nonwoven material.
[0016] Further steps may include: - Use of nonwoven materials in articles, e.g. for hygiene products, absorbent products, automotive industry, building industry, construction, filtration, medical equipment, living, ...
[0017] It should be noted that short fibres are different from long fibres: long fibres are long continuous fibres obtained by extrusion using a spinneret, whereas short fibres are shorter fibres with lengths in the mm or cm range.
[0018] Depending on the application, the weight percentage of the PSF in the nonwoven fabric obtained by the method of the present invention may vary from 5% to 100%, preferably from 10% to 98%, preferably from 15% to 95% of the nonwoven fabric. For example, a nonwoven fabric for a mattress application typically contains about 15% low melting point staple fibers and can contain up to 85% PSF, while a nonwoven fabric for a hygiene application such as an acquisition and distribution layer (ADL) in a baby diaper typically contains about 50% LMF and can contain up to about 50% PSF.
[0019] The present invention also encompasses a nonwoven material comprising 5-100 wt. % of a PSF comprising at least 0.75% PET and / or CoPET derived from recycled nonwoven fabrics, having an intrinsic viscosity (IV) (intrinsic viscosity measured as disclosed below) of less than 0.7 dl / g, wherein the nonwoven has an opacity comprised between 20% and 50%, preferably between 25% and 40%, measured according to the method described below.
[0020] The present invention also relates to an absorbent product incorporating the nonwoven material of the present invention, comprising a topsheet forming a wearer-contacting surface of the absorbent product, a backsheet, and an absorbent core and / or an acquisition and distribution layer (ADL) interposed between the topsheet and the backsheet, the absorbent product comprising a nonwoven material comprising 5% to 100% by weight of a PSF comprising at least 0.75% PET and / or CoPET derived from recycled nonwoven fabrics, and having an intrinsic viscosity (IV) (intrinsic viscosity measured as disclosed below) of less than 0.7 dl / g.
[0021] Advantageously, the nonwoven fabric in the absorbent product comprises at least 20% by weight of core / sheath or side-by-side bicomponent fibers as binder fibers, which is of particular interest when the manufacturing process includes a heating step.
[0022] Any one or more layers of the absorbent product may be a nonwoven fabric according to the present invention. Preferably, the nonwoven fabric is included in at least the ADL. The nonwoven fabric may also be included in the core as a single layer, double layer or triple layer within the core.
[0023] The process of the present invention may include the step of mixing a color dye either before the repelletizing step or before the extrusion step.
[0024] Extrusion of the blends can result in PSFs with solid or hollow cross sections with some void regions. They can have any shape, such as, but not limited to, circular, triangular, trilobal or multilobal cross sections...
[0025] The length of the resulting PSF is preferably 20 mm or more, but is not limited to this.
[0026] The invention will be better understood from the following description of some examples, with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0027] [Figure 1] 1 is a general scheme of the method of the present invention. [Diagram 2] 1 shows the production of a nonwoven fabric using recycled fibers of the present invention. [Diagram 3] 1 is a DSC scan of the fiber of Example 1 in Table 1. [Figure 4] The ADL production line is shown.
[0028] With reference to Figure 1, in step A, polyester-based nonwoven material 1 is fed to a re-pelletizer 2 to obtain recycled polyester-based pellets 3. The nonwoven material here is, for example, waste trim from a nonwoven manufacturing line. It contains 5-50% PET / coPET low melting staple fibers. Such waste is usually clean and does not need to be washed before recycling. For other sources of nonwoven waste, a pre-washing step may be required.
[0029] Repelletizers are well known in the art of plastic molding. The principle is to melt nonwoven waste into a liquid state in two stages. The first preconditioning stage dehumidifies the polymer and removes the spinning oil, then degass the liquid polymer, and then reduce the temperature while making the polymer cylindrical or spherical to form polyester granules or pellets 3.
[0030] The intrinsic viscosity (IV) values of the resulting granules are typically lower than conventional PET flake resins due to the presence of a significant proportion of LMF.
[0031] Typical IV values found are around 0.49-0.60 dl / g, while IV values for PET flakes from bottles are around 0.70-0.75 dl / g.
[0032] The IV required to spin staple fibers is 0.65-0.70 dl / g for white fibers, but can be lower for black fibers, for example about 0.62 dl / g.
[0033] A possibility to increase the IV known in the art is to add an additional SSP (Solid State Polymerization) step after repelletization, but this significantly increases the cost price of the process. Therefore, the method of the present invention preferably does not include an SSP step.
[0034] The melting temperature is an alternative characterization value of the polymer. While normal PET has a melting temperature of about 260-265°C, pellet 3 has a melting temperature a few degrees lower, i.e. 253-258°C, so for recycled material it is on average 7°C lower compared to standard material.
[0035] There are several repelletizing machine manufacturers, such as Erema, Starlinger, Moogetech, ... but there is no restriction here to use a particular machine technology.
[0036] Since the inherent viscosity of the pellets 3 is slightly too low to be directly extruded into staple fibers, in step B the pellets 3 are blended with polyester flakes 4 obtained from recycled PET bottles. The blend contains 15-35% recycled polyester-based pellets 3 and 65-85% polyester flakes 4.
[0037] The ratio of pellets 3 to flakes 4 is preferably adjusted after measuring the IV and / or melting temperature of pellets 3. The higher the temperature or IV, the greater the percentage of pellets that can be added to the blend.
[0038] The blend is made, for example, in an Oerlikon Barmag mixer, or a Neumag device, or any suitable device known to those skilled in the art.
[0039] In step C, the blend enters an extrusion unit 5 where it is extruded into polyester staple fibers (PSF). The extrusion process is a classical one in textile fiber production and is well known to those skilled in the art and can be, for example, a two-step process also known as the long spin process, or a single-step process also known as the short spin process.
[0040] The ratio in the blend, determined as a function of the pellet properties, will have some influence on the properties of the final PSF, i.e. fiber toughness, elongation, shrinkage level, ... For the process following the incorporation of the PSF into the nonwoven fabric, it is important that the PSF issued with the method of the invention falls within the technical data sheet of the "virgin" (no recycled material) PSF type.
[0041] Examples of technical properties obtained for virgin fibers compared to recycled fibers are given in Table 1 below. [Table 1]
[0042] Intrinsic viscosity (IV) here refers to the limiting viscosity number (LVN, intrinsic viscosity, IV, [η]) of polyesters based on polyethylene terephthalate (PET) in the form of fibers, granules, regranulates, preforms, foils, flakes, black, white and colored masterbatches (which may be based on PBT) in a viscometer Ubbelohde U 1a connected to an automated Lauda device for measuring the flow times of sample solutions and solvents, using the following procedure:
[0043] a) Solvent preparation - cleaning The mixture used for the measurement is made using phenol (CAS: 108-95-2) and 1,1,2,2-tetrachloroethane (CAS: 79-34-5) in a weight ratio of 1:3.
[0044] The phenol is distilled in an air cooler and the fraction at 182°C is collected.
[0045] 1,1,2,2-Tetrachloroethane is distilled at about 140 °C with an air condenser. A concentrated soda solution (about 20 ml / liter) is added to the distillation receiver in the flask. The fraction with a boiling point of 144-145 °C is collected.
[0046] b) Measurement The polyester samples are assumed to be completely dry. The finish is removed from the polyester fiber samples by washing thoroughly in distilled water and then drying completely. The black masterbatch is ground before weighing.
[0047] Weigh out 0.2500 g of sample and place this in a flask and add 25 ml of solvent from a burette. Dissolve the sample in a drying oven at 105 °C (maximum 2 hours, 30 minutes should be sufficient for fiber samples). Stir the flask contents every 5 minutes. Wait an additional 10 minutes after visually checking that the sample is dissolved. After cooling the solution, bleed it into a viscometer using sintered glass S2. Use the first part of the filtrate to flush the viscometer.
[0048] The viscometer filled with the sample solution is suspended in a thermostatic bath and heated at 30° C. for 10 min, after which the flow time of the solution is measured four times. Before measuring the sample, the flow time of the pure solvent is first measured (average from three measurements, tempera- tion 10 min, 30° C.). A Hagenbach kinetic energy correction is made for the measured times for the solution and the pure solvent: t=tm-B / A.tm A………. Capillary constant (0.03) B………. Viscometer constant (2.8) tm……..Measured flow time (s)
[0049] c) Test evaluation The intrinsic viscosity is calculated from the relative viscosity at a concentration c=1 g / 100 ml using the Huggins formula. The Huggins constant for PET under the given measurement conditions is k=0.25.
[0050] Next, ml.g -1 The intrinsic viscosity number (LVN) at is calculated using the following formula (which applies only to the experimental conditions used): t: corrected flow time of the sample t o : Corrected flow time of pure solvent
[0051] The computer-interfaced Lauda viscometer automatically performs all calculations, including flow time measurement and correction, and the laboratory operator only needs to read the LVN value.
[0052] The melt flow rate (MFR) was measured according to ASTM D1238, ISO 1133 standard methods.
[0053] The melting points were measured by DSC as typically done in situ, e.g., using a stabilization step at 25° C. followed by a temperature ramp of 16.00° C. / min to 300° C. FIG. 3 shows the DSC scan of the fiber of Example 1 in Table 1.
[0054] The fineness was measured using a VIBROSKOP device from Lenzing Instruments. Individual fibers with a defined pretension are placed in a device that uses the vibration principle to perform an automatic measurement. 20 individual fibers are measured and the value obtained is their average value.
[0055] Tensile strength (toughness) and elongation were measured using a VIBRODYN instrument manufactured by Lenzing Instruments. Individual fibers are clamped in a tearing jaw and subjected to mechanical stress at a defined speed and clamp length. A defined force pulls the fiber until it breaks. The percent elongation obtained at the moment it breaks is calculated, as well as the total force applied to the fineness ratio. 20 individual fibers are measured and the value obtained is their average value.
[0056] The shrinkage was measured after 30 minutes in hot air at a temperature of 160°C. The shrinkage is defined as the difference in length in percent before and after fixing the fiber. Five tows of 50 cm in length were measured.
[0057] The nr of crimps / inch was measured using a standardized instrument with a defined pretension. Individual fibers are fixed on a measuring base plate and the number of crimps is visually read. 20 individual fibers are measured and the obtained value is their average value.
[0058] The color values were measured with a reflectance spectrophotometer DT600 from Datacolor. This measurement uses specially prepared samples and precisely defined settings of the instrument for different types and wavelengths of light. Using the reflectance principle, the basic color coordinates (L, a, b) are determined. Three samples are measured and the value obtained is their average value. The fibers are combed and placed in a layer that is inserted into the spectrophotometer for the readout. From the readout the basic color coordinates (L, a, b) are extracted.
[0059] It was generally observed that the color values of the PSF obtained by the method of the present invention were slightly darker than the "virgin" fiber and had a stronger yellow color component.
[0060] The PSF obtained by the method of the present invention can be incorporated into any type of nonwoven fabric in the same manner as "virgin" fibers.
[0061] For example, a polyester-based thermally bonded drylaid nonwoven can be produced using 50% PSF fibers obtained by the recycling method of the present invention and 50% low melting point fibers for incorporation as an ADL (absorption and distribution layer) in a hygiene product.
[0062] For example, a polyester-based thermally bonded dry-laid nonwoven fabric can be produced using 50% PSF fiber obtained by the recycling method of the present invention, 35% standard PSF, and 15% low melting fiber for fiber filling applications.
[0063] Test 1- Thermally bonded nonwoven material for use in bedding / quilting / furniture applications. Thermally bonded nonwoven materials according to the present invention were produced for use in bedding / quilting / furniture applications.
[0064] 2, a nonwoven fabric 25 was produced according to a standard process starting from three carding machines 20, 22, and 23. Here, a cross wrapper 21 is implemented downstream of the carding machine 22. A mixing unit (not shown) is installed upstream of the carding machines to mix the fibers used for each web.
[0065] Carding is a mechanical process that loosens, cleans, and mixes fibers to produce a continuous web suitable for further processing. This is accomplished by passing the fibers between clothed, moving surfaces. This breaks up clumps and unorganized bundles of fibers and aligns the individual fibers so that they are parallel to each other. The fibers are not straight elements and are not strictly parallel, but are oriented in a common general direction overall. The fact that the fibers are not straight elements creates points of contact between the fibers, and these contact points are the bonding points during the bonding process.
[0066] Depending on the expected thickness and / or weight of the nonwoven material, multiple layers of carded fibers of the same or different composition can be layered before bonding, using techniques and equipment well known to those skilled in the art. Using multiple carding machines in parallel, usually up to three, allows working at high speeds. The resulting web is then layered before web bonding, which can be mechanical, thermal and / or chemical bonding. This also presents the advantage that the different properties of multiple fiber blends can be combined.
[0067] In this in-line configuration, the overall thickness of the nonwoven fabric depends on the thickness of the web leaving each carding machine and the number of carding machines operating in parallel. Typically, no more than three carding machines are used in parallel, and the resulting nonwoven fabric weight is about 200 g / m 2 , preferably 120 g / m 2 Furthermore, the general orientation imparted to the fibers in the carding process is maintained in the bonding process, so that the nonwoven fabric has high tear resistance in the machine direction, which is parallel to the general orientation of the fibers, and less tear resistance in the cross direction.
[0068] However, a cross-lapping step can be carried out after carding on one or more carding lines, which overlaps the web of carded fibres in several layers and also imprints a deviation in the general orientation of the fibres which differs between two successive overlaps. Cross-lapping therefore allows the production of much thicker fibres, typically 120 g / m2, than when using an in-line process. 2 The resulting nonwoven material also has high tear resistance in all directions.
[0069] The webs resulting from the three carding machines are then laminated together in a three-way oven 24 to form a single thermally bonded nonwoven fabric 25.
[0070] An optional needling step can be carried out downstream of carding and stacking before heating the overlapped web, resulting in entanglement or intermingling of the fibers in the vertical dimension. This is especially recommended when multiple carding machines are used. Vertical here refers to the direction perpendicular to the machine and cross directions disclosed in the previous paragraph, i.e. across the various layers of the web. Needling can entangle the fibers to obtain better adhesion of the web layers. Hydroentangling can be used instead of or in addition to needling. Needling and hydroentangling are techniques well known to those skilled in the art. Other reinforcing techniques can also be used, such as, for example, polymer extrusion, chemical bonding, either by knife-over-roll or any suitable coating technique, as known to those skilled in the art.
[0071] As a final step, after bonding, the nonwoven fabric is wound and packaged.
[0072] The bonding of the fibers to complete the nonwoven layer is carried out here by thermal bonding, but can also be carried out using different techniques, such as mechanical or chemical bonding. In this case, the bonding preferably includes a step of thermal bonding alone or in combination with another technique. Preferably, the nonwoven of the present invention is a dry-laid thermally bonded nonwoven. A combination of mechanical, chemical and thermal bonding can also be selected.
[0073] The blend of fibers fed to the second carding machine 22 is here a blend comprising: -Bicomponent fiber PET / CoPET 4dn-51mm, 25% - 65% PSF fibres (6dn-60mm) obtained from recycling and corresponding to the fibre mixtures of examples 1-6 in Table 1 - internal waste (fibers recovered from the edges of the web when it is cut to size and reincorporated into the blend prior to the bonding process), 10%.
[0074] The blend of fibers fed to the carding machines 20 and 23 is here a blend comprising: -Bicomponent fiber PET / CoPET 4dn-51mm, 25% -Solid PET fiber 6dn-64mm, 30% - 30% PSF fibres (6dn-60mm) obtained from recycling and corresponding to the fibre mixtures of examples 1-6 in Table 1 - internal waste (fibers recovered from the edges of the web when it is cut to size and reincorporated into the blend prior to the bonding process), 15%.
[0075] Carding machines 22 and 23 each provide webs worth 30% of the final product, while carding machine 20 provides webs worth 40% of the final nonwoven fabric. As a result, the final nonwoven fabric contains 44% recycled PSF according to the present invention. The resulting nonwoven fabric has a weight per surface area of about 150 g / m 2 It is.
[0076] Four prototypes were made. Each prototype nonwoven sample was characterized for its opacity using the following ASTM method and compared to a comparable sample made from non-recycled fibers (Thermoloft 21).
[0077] Opacity is determined by the reflectance obtained from a material using a black background as well as the reflectance obtained for the same material using a white background.
[0078] The equipment used is as follows: Hunter ColorFlex EZ Spectrophotometer (Sensor number: ColorFlex EZ 45 / 0 "CFEZ 3350") EasyMatch QC Software Colorflex EZ Standard Box: Calibration black and white tiles Green tile for additional inspection Black and white tiles for taking exams.
[0079] The device is standardized according to the manufacturer's instructions using the white, black, and green tiles provided in the Colorflex EZ standard box.
[0080] The settings are adjusted as follows: -Illuminant D65 / 10 -Observer 10°
[0081] A 125 x 125 mm sample of the nonwoven fabric can be cut and the test can be carried out according to the following procedure: -Place the sample on the device above the measuring cell.
[0082] The machine direction (MD) of the sample is aligned with the instrument and the smooth side of the sample faces downwards. -Place the white tile on the sample (white circle facing down); -Measure with a white tile; -Remove the white tile and replace it with a black tile (white circle facing down); -Measure with black tile; - Opacity is calculated and expressed here as the percentage ratio of the reading on the black plate to the reading on the white plate.
[0083] The standard method for measuring the opacity of nonwoven fabrics is given by EDANA NWSP.060.4.R0.
[0084] Opacity was measured on five sections of each sample and the average is shown below: Sample 1: 79.45% Sample 2: 76.53% Sample 3: 77.90% Sample 4: 79.62% Thermoloft 21: 80.77%.
[0085] The same four samples were characterized for dynamic load measured according to the pounding test according to ISO 3385. The results are summarized in Table 2 below. [Table 2]
[0086] The same four samples were characterized for elongation and tensile strength in both the machine direction (MD) and carding direction (CD), measured according to the test ISO 9073-3, and the results are summarized in Table 3 below. [Table 3]
[0087] The results in Tables 2 and 3 demonstrate the comparability between the reference nonwoven fabric containing no recycled fibers and the nonwoven fabric according to the invention.
[0088] Similarly, about 300 g / m 2 Nonwovens having a weight per surface area of 100 g / m2 have been produced and compared to an equivalent Thermoloft 21 reference.
[0089] The results are summarized in Tables 4 and 5. [Table 4] [Table 5]
[0090] Tests 2 and 3 - Thermally bonded nonwoven materials for use in hygiene products The fibers obtained in examples 1 to 3 are used to prepare nonwovens for hygiene, in particular to be used as ADLs and / or absorbent cores to be incorporated into absorbent products. These nonwovens are compared with the standard product DW T161 AF manufactured by TWE for ADLs. The specifications of this material are given in Table 2 below, together with the properties of the nonwovens obtained in tests 2 and 3.
[0091] In Test 2, a fiber blend was prepared using 50% fiber from Example 3 in Table 1 and 50% melt bicomponent fiber.
[0092] In Test 3, a fiber blend was prepared using 50% fibers from Examples 1 and 2 of Table 1 (mixture) and 50% melt bicomponent fiber.
[0093] The nonwoven fabrics were produced using standard methods (i.e., using one, two or three carding machines and thermal bonding, for example as shown in FIG. 4).
[0094] FIG. 4 shows a typical ADL production line with three carding machines 41, 42, and 43, the use of the third machine 43 being optional here. Each carding machine is connected to a bale opener 51, 52, and 53, respectively, for providing fibers (each carding machine can be connected to several bale openers nt shown for clarity purposes). Here, fiber silos and inspection units are provided between each bale opener and its corresponding carding machine, as is customary in the art. The webs produced by carding machines 41, 42, and optionally 43 are overlapped and combined into a nonwoven fabric before entering flat belt oven 40. The nonwoven fabric is then cooled in cooling zone 44, followed by an inspection step before being wound up by winder 45. The nonwoven fabric roll is further sized or conditioned in step 46 before being packaged in step 47.
[0095] The physical properties of the obtained nonwoven fabric were evaluated according to the standard Edana procedure and are shown in Table 6.
[0096] The absorbency properties of the nonwoven fabrics of Tests 2 and 3 were also measured according to the standard Edana procedure and are shown in Table 7.
[0097] The properties shown in Tables 6 and 7 are measured according to standard methods as set forth by Edana unless otherwise stated.
[0098] As can be seen from Table 6, nonwoven fabrics made from recycled PFS have properties that fall within the specification range of comparable nonwoven fabrics made from virgin fibers. Opacity and tensile strength in the same range are above the average expected values. [Table 6]
[0099] Tensile strength is the maximum tensile stress expressed as force per unit cross-sectional area of an unstrained specimen, e.g., Newtons per square millimeter, measured in accordance with Edana Standard 110.4.R0(15). [Table A] The thickness is measured according to Edana assay WSP 120.6.R0(15) while subjecting the material to various pressures.
[0100] Elongation was measured according to Edana assay WSP 110.4.R0 (15).
[0101] Opacity is measured according to the method described above. [Table 7]
[0102] Strike-through time is the time it takes for a known amount of liquid (e.g., simulated urine) applied to the surface of a specimen of nonwoven cover stock in contact with an underlying standard absorbent pad to pass through the nonwoven. It was measured using EDANA Assay WSP 70.3.R1(19). Repeated strike-through times were measured according to EDANA Assay WSP 70.7.R1(19).
[0103] The Wetback test is intended to determine the ability of a diaper coverstock to prevent backflow onto the skin of liquid that has already penetrated the coverstock. It was measured according to EDANA assay WSP 80.10R1(19).
[0104] Wetback after repeated strike-through (ST) was measured according to Edana assay WSP 70.8.R1 ( 19 ).
[0105] Runoff quantifies the amount of liquid that runs down a nonwoven fabric when a specific amount is poured into the liquid at an angle. It is measured according to Edana assay WSP 080.9.R1(19).
[0106] As can be seen from the results in Tables 6 and 7, the ADL nonwovens incorporating recycled PSF meet the specifications set for the standard product. Some specifications even exceed the performance of the reference material. In particular, the wetback and strikethrough properties are well below the upper limits allowed.
[0107] These are non-limiting examples of fiber ratios, manufacturing techniques and applications of the fibers of the present invention.
[0108] Nonwoven manufacturing techniques in which PSF can be used include, but are not limited to, the following: -Mechanically bonded nonwoven fabrics by needling -Mechanically bonded nonwoven fabrics by hydroentangling -Resin-bonded nonwoven fabrics using a foam bath -Spray-bonded nonwoven fabrics using spray resin -Thermal bonded nonwoven fabrics made from LMF blends -Stitchbonded nonwoven fabric, -others...
Claims
1. A method for recycling polyester-based nonwoven fabrics containing 5-50% PET and coPET low melting staple fibers, having at least a sheath component that melts at a temperature of about 180°C or less, comprising: feeding the polyester nonwoven fabric for recycling to a re-pelletizer to obtain recycled polyester pellets; mixing the resulting pellets with polyester flake to form a blend containing 15-35% recycled polyester pellets and 65-85% polyester flake; and extruding the blend into polyester staple fibers (PSF) having an intrinsic viscosity (IV) of less than 0.7 dl / g. A method comprising:
2. The method of claim 1 , wherein the polyester flake is derived from recycled PET bottles.
3. 3. The method of claim 1 or 2, wherein the PSF contains 0.5-50% PET and / or coPET.
4. Incorporating the PSF into a web of fibers to produce a nonwoven material The method of any one of claims 1 to 3, further comprising:
5. Using said nonwoven material in articles, such as hygiene products, absorbent products, articles for the automotive industry, etc. The method of claim 4 further comprising:
6. Polyester staple fibres (PSF) obtainable by the process according to any one of claims 1 to 3, having an intrinsic viscosity (IV) of less than 0.7 dl / g, preferably between 0.6 and 0.7 dl / g.
7. 7. The polyester staple fiber (PSF) according to claim 6, comprising at least 0.75% PET and / or CoPET derived from recycled nonwoven fabrics.
8. 10. A nonwoven material comprising 5-100% by weight of the PSF of claim 7 and having an opacity comprised between 20% and 50%, said opacity being determined as a percentage ratio of a reflectance obtained from the material on a black background to said reflectance obtained for the same material on a white background.
9. 1. An absorbent product comprising: a topsheet forming a surface of the absorbent product that contacts a wearer; a backsheet; and an absorbent core and / or an acquisition and distribution layer (ADL) interposed between the topsheet and the backsheet, the absorbent product comprising a nonwoven material, the nonwoven material comprising at least 0.75% PET and / or CoPET derived from recycled nonwoven fabrics, and 5% to 100% by weight of a PSF having an intrinsic viscosity (IV) of less than 0.7 dl / g.
10. 10. The absorbent product of claim 9, wherein said nonwoven fabric comprises at least 20% by weight of core / sheath bicomponent fibers.
11. 11. The absorbent product of claim 9 or 10, wherein the nonwoven is comprised at least in the ADL.
12. 11. The absorbent product according to claim 9 or 10, wherein the nonwoven is comprised at least in the core, such as a single-layer, double-layer or triple-layer core.
13. The absorbent product according to any one of claims 9 to 12, wherein the nonwoven is provided between the topsheet and the absorbent core.
14. 9. Use of the nonwoven fabric according to claim 8 in articles for automotive applications, construction, bedding, quilting and / or furniture applications, or in hygiene and / or medical articles.